Comparison of the efficacy of non-pharmacological interventions during the heel stick procedure on pain level, duration of crying, and voice decibel of newborns: a randomized controlled trial - Pınar Duru; Zehra Akkoca; Özlem Örsal (Perinatal Medicine Foundation, 2023)
Objective: To compare the efficacy of different non-pharmacological interventions (kangaroo care, cuddling, playing white noise, ambient sound) applied to newborns during the heel stick procedure on newborns' pain level, duration of crying, and voice decibel. Methods: This is a prospective, randomized controlled trial including pre- and post-tests of four groups. The setting is a neonatal intensive care unit in Türkiye. One hundred and thirty-six newborns were recruited. Newborns were randomly assigned to four groups (i) kangaroo care, (ii) cuddling, (iii) white noise, and (iv) ambient sound. Pain measures were recorded 1 minute before, during, and 3 minutes after blood collection based on the Neonatal Infant Pain Scale (NIPS). Results: There was a significant difference between the pain levels (χ2=16.910, p=.001) and durations of crying (χ2=13.888, p=.003) during the heel stick procedure of the newborns depending on the non-pharmacological intervention. The pain levels of newborns who received kangaroo care were significantly lower compared to those who were listened to ambient sound during the procedure. The newborns' durations of crying who received kangaroo care and who were lapped by their mothers during the heel stick procedure were also lower than those who are listened to ambient sound. There was no significant difference between the highest sound decibel levels of newborns after the procedure due to the non-pharmacological intervention applied during the heel stick procedure. Conclusion: Kangaroo care was more effective in reducing pain level and duration of crying. The non-pharmacological interventions had no effects on the highest sound decibel levels of newborns.